Tahlîlu Khurûji Uslûbi Istifhậmi “Kayfa” ‘an Ma’nậhu al-Haqîqiy fil Qur’ận/ تحليل خروج اسلوب الاستفهام "كيف " عن معناه الحقيقي في القران - pasaribu, mudiul hayat; hulawa, djeprin e. (Al-Manar, 2024)
The purpose of this study was to examine the deviations of Uslub Istifham with Thoriqah Kaifa from the original meaning in Al-Qur’an. It was a qualitative research conducted using library resources. The focus of the study was on Uslub Istifham using Kaifa in Al-Qur’an. Both primary and secondary sources related to the research subject were utilized. Data collection involved the use of library research, observation, and reading relevant books. Content analysis using tables was employed to analyze the gathered data. The results indicated that there were 80 verses in the form of Uslub Istifham using Kaifa in Al-Qur'an. Of the 80 verses, 70 showed different meanings from the original, while 10 accurately conveyed the intended meaning. The variations in the interpretation of Uslub Istifham were determined through analysis and included: 1) prohibition, 2) denial, 3) decree, 4) reproach, 5) humiliation, 6) glorifying, 7) asking late, 8) wondering, 9) generalizing, 10) expecting, 11) longing.